Pengenalan Objek Museum dan Monumen PETA Menggunakan Markerless Augmented Reality Berbasis Android - Firdaus, Yoga Hardi; Jaenudin , Jejen; Fajri , Hersanto (JUSS (Jurnal Sains dan Sistem Informasi), 2020)
PETA Museum and Monument is a museum that collects various kinds of historical objects that are very important to the Indonesian people. To keep up with the times, there is an idea to apply Augmented Reality technology which is expected to make it easier for museums to introduce objects to the public. Augmented Reality is a technology that combines an artificial engineering object that has been made previously with the real world in real time. Artificial engineering objects can be in the form of 2-dimensional images or 3-dimensional images, but 2-dimensional images can only be seen from one direction, while 3-dimensional images can be seen from all directions, for example the front, left side, back, right side, up and down . There are several Augmented Reality methods for bringing up engineering objects, including using the marker method where the method requires a marker to bring up the object, but Augmented Reality has been developed to produce a new method that makes it easier for users, namely the Markerless method which is unnecessary again a marker for displaying engineering objects because the system has recognized various surrounding environmental surfaces such as recognizing object shapes, face shapes, plane shapes and so on. So that objects can be displayed in various places without the need for tools such as markers or box-shaped objects. Based on statcounter.com data, it is known that in 2020 the largest operating system in Indonesia is the Android operating system with a market share of 92.3% and is supported by data from statista.com which shows smartphone users in Indonesia are 81.87 million users. The use of Augmented Reality in the introduction of museum objects and map monuments is expected to assist museums in the introduction of using technology.